Kaji Eksperimental Performansi Mesin Pendingin Kompresi Uap dengan Menggunakan Refrigeran Hidrokarbon (Hcr12) Sebagai Alternatif Refrigeran Pengganti R12 dengan Sistem Penggantian Langsung (Drop In Substitute) - Afdhal Kurniawan Mainil (JURNAL MECHANICAL, 2012)
AbstractType of refrigerant the most recognized and the most used today in the vapor compression cycle is R-12 refrigerant (halocarbon group), which is technically quite good.  The refrigerant also has low toxicity and low flammable. But, in the mid 1970’s known that chlorine has contained in the refrigerant were released into the environment could damage of ozone in the stratosphere and caused greenhouse effect. Because of that, it using has stopped. An alternative refrigerant is hydrocarbon refrigerant (HCR) and one of it is hydrocarbon-12 (HCR-12). HCR-12 have several advantages, besides friendly environmental because have low global warming effect and low destruction of ozone, this type of refrigerator can be used as direct changer on the refrigerant machine so no needed compressor replacement and more efficient electric energy than R-12. In this research, did a study experimental to compared R-12 with HCR-12 with used vapor compression cooler machine. The result of measurement have been get performance of vapor compression cooler machine COPR (Coefficient of Performance Refrigeration) and COPHP (Coefficient of Performance Heat Pump) for R-12 and HCR-12 relatively are 2.4 – 9.8 (COPR) and 3.4 – 10.8 (COPHP) and 6.4 – 14.1(COPR) and 7.4 – 15.1 (COPHP). Performance of vapor compression cooler machine COPR and COPHP have tendency increase with increase rate of flow of refrigerant until 0.035 for R-12 and 0.014 for HCR-12. Performance vapor compression cooler machine of COPR increase if absorbed of heat (Qe) by evaporator increase and COPHP increase if released of heat (Qk) by condenser increase. According of the results concluded that performance of vapor compression cooler machine with hydrocarbon-12 (HCR-12) better than R-12.Key words : refrigerant, hydrocarbon, R-12, ODP, GWP.